2011
DOI: 10.1044/1092-4388(2011/10-0274)
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Voice Therapy on Relative Fundamental Frequency During Voicing Offset and Onset in Patients With Vocal Hyperfunction

Abstract: Purpose The purpose of this study was to determine if the relative fundamental frequency (RFF) surrounding a voiceless consonant in patients with hyperfunctionally related voice disorders would normalize after a successful course of voice therapy. Method Pre- and post-therapy measurements of RFF were compared in 16 subjects undergoing voice therapy for voice disorders associated with vocal hyperfunction. Results A two-way ANOVA showed a statistically significant effect of both cycle of vibration near the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 26 publications
1
53
0
3
Order By: Relevance
“…This corroborates previous findings that have suggested that while offset RFF may be well-suited to detection of mild changes in vocal effort, onset RFF is more sensitive to differences in the level of vocal effort (Eadie & Stepp, 2013; Stepp et al, 2012). A simple model has been proposed to explain the physiological mechanisms behind RFF (Stepp et al, 2011; Watson, 1998). The model involves a combination of vocal fold kinematics, aerodynamics, and tension, incorporating the observation that the activity of the cricothyroid muscle tends to be high immediately preceding, during, and following the voiceless consonant (Löfqvist, Baer, McGarr, & Story, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This corroborates previous findings that have suggested that while offset RFF may be well-suited to detection of mild changes in vocal effort, onset RFF is more sensitive to differences in the level of vocal effort (Eadie & Stepp, 2013; Stepp et al, 2012). A simple model has been proposed to explain the physiological mechanisms behind RFF (Stepp et al, 2011; Watson, 1998). The model involves a combination of vocal fold kinematics, aerodynamics, and tension, incorporating the observation that the activity of the cricothyroid muscle tends to be high immediately preceding, during, and following the voiceless consonant (Löfqvist, Baer, McGarr, & Story, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in individuals with vocal hyperfunction, both offset and onset RFF tend to be lower in comparison to individuals with healthy voices. The RFF of individuals with vocal hyperfunction normalizes after successful voice therapy (Stepp, Merchant, Heaton, & Hillman, 2011), but has been found not to significantly change following surgery (Stepp et al, 2010). These results suggest that the measure is sensitive to the functional nature of vocal hyperfunction, which may or may not be accompanied by organic pathologies (Hillman et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with VH and healthy controls have been shown to have differences in RFF values Stepp, Hillman, et al, 2010a;Stepp et al, 2012). Stepp, Merchant, et al (2011) have previously proposed a model incorporating a simple summation of vocal fold tension, aerodynamic factors, and abductory factors to explain these differences. The authors proposed that the lowered RFF noted in individuals with VH could be accounted for by a simple reduction in the effects of tension, presumably due to higher baseline laryngeal tension in individuals with VH.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work examining differences in RFF values demonstrated that these values remain unchanged in individuals who have received surgery to remove vocal nodules or vocal polyps (e.g., structural change; Stepp, Hillman, et al, 2010a). RFF values were, however, shown to increase in individuals with VH after a successful course of voice therapy (i.e., functional change; Stepp, Merchant, Heaton, & Hillman, 2011), suggesting that these changes in RFF values may be due to functional differences in voice use rather than representative of structural differences. These results support the use of RFF to examine the potential functional differences between these two subtypes of VH.…”
Section: T He Clinical Diagnosis Of Vocal Hyperfunction (Vh)mentioning
confidence: 99%
See 1 more Smart Citation